Kelompok Usaha Pengolahan Ikan Desa Pasar Banggi, Kecamatan Rembang, dalam Upaya Meningkatkan Kualitas Produksi Olahan Ikan Asap - Rikah Rikah (Universitas Islam Nahdlatul Ulama Jepara, 2020)
Smoked fish processing business in Pasar Banggi Village, Rembang District, Rembang Regency with Karya Mina smoked fish processing partner. The fish fogging process is done by first drying the fish in an open area. Pasar Banggi Village is a village located around the tourist area and is a center for souvenirs from marine products, one of which is smoked fish. The purpose of the Community Partnership Program (PKM) is to increase community income through increased quality and quantity of smoked fish production. The method used in the Community Partnership Program (PKM) is through socialization / counseling, management training, simple financial accounting and online marketing and business assistance. The results of the Community Partnership Program (PKM) include 1) an increase in the role of smoked fish business group members and business networks, 2) the realization of environmentally friendly smoked fish processing equipment / machines whose goal is to minimize air pollution caused by traditional / conventional fumigation of fish and maintain the quality and hygiene of processed fish products in the form of smoked fish.